Celebrating 25 years of archaeological research at the Danish Institute at Athens - Winther-Jacobsen, Kristina; Frederiksen, Rune; Handberg, Søren (Proceedings of the Danish Institute at Athens, 2017)
The article gives a brief introduction to the Danish archaeological field projects in Kefallenia, Rhodes, Chalkis, Kalydon, Piraeus, Khania, Lechaion, Delphi and Sikyon as well as on Mount Pelion conducted through The Danish Institute at Athens.